PENGARUH LATIHAN KEGEL TERHADAP FREKUENSI INKONTINENSIA URINE PADA LANSIA DI UNIT REHABILITASI SOSIAL MARGO MUKTI REMBANG - Sutarmi Sutarmi; Tutik Setyowati; Yuni Astuti (Poltekkes Kemenkes Semarang, 2016)
The purpose of this study was to determine the influence of the Kegel exercise on frequency of urinary incontinence in the elderly. This study used a quasi -experimental with one group pre and post test study design, conducted on 27 respondents selected by purposive sampling technique. Respondents were divided into three groups which were the first group with frequency of exercise 2 times, the second group with 3 times and the third group 4 times a day for six weeks. Data on the frequency of urinary incontinence were collected in pre and post intervention Kegel exercise. Data were analyzed using t-test (paired t-test).The results of the study revealed that group I , II and III in sequence value of t-count 21.92, t=11,418 and t=15.307 with P values p=0, 00. Further comparisons between the three groups showed group III showed the mean frequency of urinary incontinence at least. It can be concluded that Kegel exercises affect the decrease in the frequency of urinary incontinence in the elderly, and it is suggested that Kegel exercises should be done regularly.